A new heligmonellid species (Nematoda) from oligoryzomys nigripes (Rodentia: Sigmodontinae) in the Atlantic Forest, Brazil - Souza, Joyce G.R. (2009)
Fil: Souza, Joyce G.R.. Laboratório de Biologia e Parasitologia de Mamíferos Silvestres Reservatórios. Instituto Oswaldo Cruz. FIOCRUZ. Rio de Janeiro; Brazil